Role of loop entropy in the force induced melting of DNA hairpin - Mishra G.; Giri D.; Li M.S.; Kumar S. (My University, 2025)
Dynamics of a single stranded DNA, which can form a hairpin have been studied in the constant force ensemble. Using Langevin dynamics simulations, we obtained the force-temperature diagram, which differs from the theoretical prediction based on the lattice model. Probability analysis of the extreme bases of the stem revealed that at high temperature, the hairpin to coil transition is entropy dominated and the loop contributes significantly in its opening. However, at low temperature, the transition is force driven and the hairpin opens from the stem side. It is shown that the elastic energy plays a crucial role at high force. As a result, the force-temperature diagram differs significantly with the theoretical prediction. © 2011 American Institute of Physics.